Traces of devotion in the Pulau Sewangi Village - Muhammad Yunus (UMBanjarmasin, 2021)
Pulau Sewangi Village is a village located in Pulau Alalak District, Barito Kuala Regency. This village has a characteristic where the livelihood is shipbuilding. So from an economic point of view, it's good. However, in terms of health, education, facilities and infrastructure are very lacking. Therefore, place observations and create work programs that are useful for the local community. People's understanding of the dangers of the Covid-19 virus is still minimal, therefore socialization and education are carried out as a form of preventing the spread of the virus. The facilities and infrastructure in this village are inadequate because many important facilities are not available such as Puskesmas, pharmacies, junior high schools and high schools, making it difficult for residents who have an interest in this. With work programs such as health checks, small schools, and education on the prevention of the Covid-19 virus, as well as other programs, it is hoped that they can provide useful value for the local community.